Strategi Rekrutmen Tenaga Pendidik dalam Meningkatkan Kualitas Madrasah di Madrasah Aliyah Walisongo Gending Probolinggo - Ubaidillah, Muhammad; Afifin, Muhammad Odik (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
This study aims to explain and analyze the recruitment strategies for educators at Madrasah Aliyah Walisongo Gending Probolinggo. The research employs a qualitative approach, with data collected through observation, interviews, and documentation methods. The obtained data is analyzed through data reduction, data presentation, and conclusion drawing. The field research results indicate that the recruitment system for educators involves several stages determined by the madrasah, including program planning and analysis based on the needs of the educators, starting from administrative selection, interviews, teaching practice tests, and training. The selected candidates must meet the needs of the madrasah and possess adequate skills, thereby enhancing the quality of education at Madrasah Aliyah Walisongo Gending Probolinggo.